Communication Skills in Academic Monologue Discourse. Empirical and Applied Perspectives - Pérez-Llantada, Carmen (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This paper discusses those metadiscourse techniques that help develop learners’ communication skills in university courses of English for Academic Purposes (EAP). Firstly, the theoretical framework of the concept of metadiscourse (Hyland 1998, Mauranen 1998&2000, Swales 2001, Thompson 2003) is revised and then applied to those language strategies for effective communication which are covered by current bibliographical references on academic listening and speaking in these courses. In the second part of the article, an empirical analysis illustrates how metadiscourse in EAP monologic speech is targeted to enhance both the cognitive (Wilson & Sperber 1998) and interpersonal aspects of language use (Ventola & Mauranen 1991, Johns 1997, Hyland 2000). The third part of the paper details experimental research concerning suitable pedagogical procedures for teaching/learning spoken metadiscourse through a genre-based approach (Ferguson 2002). The article concludes with a reflection on the need to approach tertiary education syllabuses from the perspective of a social theory of language and communication.